2023
DOI: 10.1097/mao.0000000000003824
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Patient Information for Cholesteatoma on the Video Sharing Platform YouTube

Abstract: IntroductionCholesteatoma is common chronic ear condition that usually requires surgical treatment and long-term follow-up. The Internet helps patients find information about their medical conditions and assists in shared clinical decision making. This work aims to assess the quality of information on YouTube for cholesteatoma. We aim to assess the quality of the most popular cholesteatoma videos on YouTube using recognized scoring systems and determine if quality correlated with video likes and views.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
(34 reference statements)
3
7
0
Order By: Relevance
“…YouTube's algorithm favors group accounts, resulting in over half of its uploaders being non-pro t organizations. This nding on YouTube is in agreement with previous studies on other diseases [2,5,9,20]. TikTok, with its stringent certi cation requirements, only allows certi ed attending/associate/chief doctors from grade 3 and rst-class hospitals (A hospital ranking system in China.…”
Section: Principal Ndingssupporting
confidence: 89%
See 1 more Smart Citation
“…YouTube's algorithm favors group accounts, resulting in over half of its uploaders being non-pro t organizations. This nding on YouTube is in agreement with previous studies on other diseases [2,5,9,20]. TikTok, with its stringent certi cation requirements, only allows certi ed attending/associate/chief doctors from grade 3 and rst-class hospitals (A hospital ranking system in China.…”
Section: Principal Ndingssupporting
confidence: 89%
“…In recent decades, digital video, as an important carrier of information, has been widely used in patients' education. In otorhinolaryngology, YouTube and/or TikTok content has been investigated for the educational value of videos about cholesteatoma [9], pediatric tonsillectomy [10], middle ear ventilation tubes [10], rhinoplasty [12], tinnitus [13], and thyroid cancer [4,14,15]. Yet, the quality evaluation of videos related to laryngeal cancer remains absent.…”
Section: Principal Ndingsmentioning
confidence: 99%
“…Various medical information is being provided through YouTube videos, and patients can easily access this video clips. In the otolaryngology fields, the educational benefit of YouTube videos about cholesteatoma, tonsillectomy, ventilation tubes for serous otitis media, rhinoplasty, and thyroid cancer had been examined 6 , 8 , 10 , 16 18 . A recent study analyzing YouTube videos related to cholesteatoma revealed that the educational level of these videos was extremely low, and the content was reported to lack evidence-based information 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea as well, according to an update from Google's advertising resources, as of early 2023, the number of YouTube users in South Korea was estimated at 46 million, representing 88.8% of the total population. A recent systematic review postulated that YouTube has emerged as a platform for promoting unscientific therapies and drugs that lack approval from appropriate regulatory process 7 , 8 . Likewise, although the number of YouTube videos about tinnitus has increased significantly, the reliability and accuracy of these videos have not been thoroughly evaluated, indicating a need for careful assessment of the information presented by YouTube.…”
Section: Introductionmentioning
confidence: 99%
“…However, the freedom of anyone to post videos has led to a mix of video content and a lack of professional review [20]. Therefore, it is crucial to assess the quality of the information delivered [21][22][23][24][25]. To our knowledge, no previous studies have investigated the use of YouTube™ as a source of video education for the prevention of valproic acid use in women during pregnancy.…”
Section: Introductionmentioning
confidence: 99%